International exchange of information and taxpayers' rights: opposing forces or two sides of the same coin? An analysis of the legislative protection in Kenya of taxpayers' rights to privacy and confidentiality - Musibi, Prisca Eleanor (Department of Commercial Law, 2023)
Domestic Resource Mobilisation (DRM) has since 2015's Addis Ababa Action Agenda come to the fore as one of the critical avenues for developing countries to raise the resources required to fund the implementation of the Sustainable Development Goals. However, Illicit Financial Flows (IFFs) continue to undermine these DRM efforts, especially in Africa. Increased transparency in tax through mechanisms such as the cross-border collaboration of tax administrations through the exchange of tax information has been put forward as one of the ways the issue of IFFs can be tackled. The Multilateral Convention on the Mutual Administrative Assistance in Tax Matters (MCAA), as amended by the 2010 protocol, is now the most comprehensive multilateral instrument available for all forms of tax co-operation to tackle tax evasion and avoidance. This is because it is possible to establish an assistance relationship with each jurisdiction signed onto the MCAA on sign-up. Regarding tax information exchange, for countries such as Kenya with a lean network of Agreements for the Avoidance of Double Taxation, the utility cannot be overemphasised. The possibility of this vast amount of information exchange raises the issue of taxpayers' rights in relation to said information. Article 21 of the MCAA provides for the protection of persons and limits to the obligation to assist. However, this protection of rights is pegged on the domestic law provisions of the specific jurisdiction concerned. Thus, by implication, the more robustly taxpayers' rights are protected under a jurisdiction's domestic law, the more confidently requested parties would be in supplying information. This dissertation seeks to analyse Kenya's legislative framework to determine the protection available for taxpayers' rights. The key finding from this analysis is that, save for provisions on the non-disclosure of confidential information, there is a general lack of explicit provisions promoting the protection of taxpayers' rights within taxation legislation. Protection is imputed through the reading of non-taxation legislation. Following this finding, this dissertation provides recommendations of legislative reforms that can be undertaken in order to provide more robust protection of taxpayers' rights.